Environmental-friendly tri-fuel emulsion - Hagos, F. Y.; M. Mukhtar, N. Awalludin; M. M., Noor; R., Mamat; Abdul Adam, Abdullah (2018)
Monitoring tool wear in machining processes is one of the critical factors in reducing downtime and maximizing profitability and productivity. Tool condition monitoring is gaining more attention in automated manufacturing processes in recent times. 20% of machining downtime is reported to be due to tool wear, which causes surface deterioration and can be detrimental to machine health.